Genetic similarity among landraces and improved cultivars of Phaseolus vulgaris L. using microsatellite markers (Bioagro, 2020)
The base of the breeding programs are variable populations created by the crossing between divergent parents. Genetic similarity data estimated from molecular markers can be used to select such parental genotypes. The objective of the present work was to estimate the genetic similarity between landraces and improved cultivars of common bean using microsatellite markers (SSR). Thirty genotypes were evaluated: 12 landrace and 18 improved. The alleles were identified by locus, the percentage of allelic frequencies was calculated and polymorphic information content (PIC) was determined. With the recording of the presence (1) and absence (0) of bands, a binary matrix was obtained, used for the analysis of similarity by the UPGMA method. In parallel, a principal coordinate analysis was carried out. Of the 20 SSR used, 16 were polymorphic, which allowed to discriminate the similarity between the cultivars. The average PIC of the global population and the different types of cultivars evaluated showed little genetic polymorphism among the 30 cultivars, demonstrating that the genetic base of the common bean is narrow. The analysis of similarity allowed the conformation of 6 groups of cultivars, standing out the premises I-2363 and I-2294 that integrated a single group. The rest of the genotypes were organized mostly by groups of landrace, commercial and advanced lines. The variation between the cultivars was similar, although there is a variability different to the commercial cultivars of current use that can be exploited in the breeding programs of the crop.
Keywords: Genetic diversity; genotype; molecular markers